IMPROVING KNOWLEDGE OF HIJAIYAH LETTERS THROUGH THE UTSMANI METHOD AND BAGHDADI METHOD - Hinggil Permana; Rina Syafrida (Jurusan PIAUD IAIN Syekh Nurjati Cirebon, 2019)
The problem in this research is whether using the Utsmani method and the Baghdadi method can increase the recognition of hijaiyah letters for early childhood. This research was conducted at RA Syaroful 'Ulum Cikakak Sukabumi West Java with a total of 32 students. This type of research used in this study is descriptive qualitative. This study proves that the use of the Utsmani method and the Baghdadi method can improve the recognition skills of hijaiyah letters for early childhood, this can be known after an evaluation of various learning methods.